The Role of Diagnostic Imaging in Pediatric Tuberculosis with Severe Malnutrition: A Systematic Review - Isabella Mebang; Patrick Luckend Sahusilawane; Oktavia Henny (The International Journal of Medical Science and Health Research, 2025)
Introduction: The syndemic of pediatric tuberculosis (TB) and severe acute malnutrition (SAM) represents a major global health crisis, characterized by a vicious cycle of immunological impairment and metabolic decline. The diagnosis of TB in this vulnerable population is notoriously difficult due to overlapping clinical features and the blunted immune responses that render conventional tests unreliable. Consequently, diagnostic imaging assumes a pivotal role in clinical decision-making. This review systematically evaluates the evidence for the role of various imaging modalities in this context. Methods: A systematic search was conducted across PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library for original research articles published up to October 2024. Studies were included if they investigated the use of chest radiography (CXR), computed tomography (CT), or point-of-care ultrasound (POCUS) for diagnosing TB in children under 15 years with concurrent SAM. Data on study design, population characteristics, imaging findings, and diagnostic outcomes were extracted. The methodological quality of the included studies was appraised using the Cochrane Risk of Bias tool. Results: Seventeen studies met the inclusion criteria, predominantly from high-burden settings in Africa and Asia. The prevalence of TB in hospitalized SAM cohorts ranged widely, from 1.6% to 44%. CXR was the most common modality, frequently revealing non-specific findings such as consolidation, but also demonstrating a higher prevalence of severe disease patterns like cavitation in malnourished children. CT offered superior anatomical detail for lymphadenopathy and parenchymal disease but was infrequently used. Evidence for POCUS was nascent and conflicting; while some studies integrated it successfully into diagnostic algorithms to detect extrapulmonary features, others found no specific sonographic findings associated with TB. Discussion: The synthesized evidence confirms that imaging is indispensable for TB diagnosis in children with SAM. However, malnutrition significantly alters the radiological presentation, often mimicking severe bacterial pneumonia or presenting with "adult-type" features like cavitation, which complicates interpretation. While CT provides definitive characterization in ambiguous cases, its utility is limited by accessibility. The inconsistent findings for POCUS highlight an urgent need for standardized protocols. The most significant trend is the integration of imaging into multi-parameter Treatment Decision Algorithms (TDAs), which have shown superior diagnostic yield and cost-effectiveness compared to standard care. Conclusion: Diagnostic imaging is a cornerstone of TB diagnosis in children with SAM, but no single modality is sufficient. A high index of suspicion is required, and interpretation must account for the altered disease patterns caused by malnutrition. An integrated, multi-modal approach, guided by validated clinical algorithms that incorporate imaging findings, represents the most effective strategy. Future research should focus on validating standardized POCUS protocols and evaluating the long-term utility of imaging in this population.